2015
DOI: 10.1149/2.0771514jes
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Electrodeposition of Elemental Germanium onto Titanium Nitride Substrates

Abstract: We report the electrodeposition of germanium from supercritical difluoromethane (sc-CH 2 F 2 ) at 19 MPa and 358 K using [N n Bu 4 ] [GeCl 3 ]. Voltammetry shows a classic nucleation loop on the first anodic scan with a high nucleation overpotential for germanium on TiN. In all cases the deposition appears to be kinetically limited by a coupled, potential independent, chemical step. Films of germanium were deposited at a range of potentials. At high overpotentials the films were dendritic and poorly adherent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Note that both plating rates are considerably larger than that obtained previously for the equivalent chloride containing electrolyte (ca. 0.4 μm hr −1 ) and are comparable with deposition rates reported for ionic liquids at room temperature . However, the deposition rate is lower than that reported for the deposition at elevated temperature from ionic liquid reported by Wu et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that both plating rates are considerably larger than that obtained previously for the equivalent chloride containing electrolyte (ca. 0.4 μm hr −1 ) and are comparable with deposition rates reported for ionic liquids at room temperature . However, the deposition rate is lower than that reported for the deposition at elevated temperature from ionic liquid reported by Wu et al .…”
Section: Resultsmentioning
confidence: 99%
“…The redox potentials for the onset of reduction of the three tri‐halides follow the trend for the Ge−X bond strength [GeCl 3 ] − −0.71 V, [GeBr 3 ] − −0.28 V, [GeI 3 ] − −0.23 V (all vs. Ag|LaF 3 ), with the iodide being the most easily reduced. This trend is consistent with earlier studies of these complexes in liquid dichloromethane …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These works showed that despite being possible to electrodeposit germanium from ionic liquids, there were several issues: the germanium sources are poorly soluble in the ionic liquids, non-standard experimental setups had to be used to cope with the volatility of the most common germanium compounds and deposition rates are low under standard conditions. In another approach, Bartlett et al electrodeposited amorphous germanium from liquid CH 3 [20,21]. Albeit successful, this approach presents some drawbacks: on the one hand, the need of a high pressure cell, which increases the complexity of the experiment and decreases output.…”
Section: Introductionmentioning
confidence: 99%